ANALISIS NON PERFORMING LOAN DAN LOAN TO DEPOSIT RATIO TERHADAP PROFITABILITAS BANK PERKREDITAN RAKYAT DI KOTA BATAM - Susanto; Sunarto Wage (LPPM Universitas Putera Batam, 2022)
This study aims to determine the efficiency of BPR profitability in the city of Batam which was tested using the Non Performing Loan and Loan Deposit Ratio variables. profitability in this study using ROA. The population of this study includes BPR in Batam city and 28 BPR selected as a sample of the city studied according to the criteria by using rational sampling technique. Data analysis in this study includes multiple linear regression analysis. Based on the results of the ad dets test, it has a significant negative effect on profitability according to the test showing a significant value of 0.000 t Tale 1.98137. The loan deposit ratio has no significant effect on profitability on the results of asis if the test shows a significant value of 0.23 > 0.05 and the account is 1.175 or higher; The story of 1.98137. Based on the test results indicate that the NPL and LDR simultaneously have a significant effect on profitability with a significance value of 0.000 and 0.05.